“God in the tundra”, “God in the chum” and “God in the soul”. How soviet secularization influenced the religiosity of the nenets (NAO) - Дарья Егорова (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия, 2022)
The modern processes of national revival of the minor indigenous people of Russia include not only a return to the origins of national culture, they also have a religious component. Attempts are being made everywhere to reproduce ancient religious traditions and cult practices. However, the transformation of the religious state that took place during the XX century has not been studied enough, in particular, we have little reliable data on how the active introduction of Soviet ideology influenced this. This article examines the secularization processes that took place during the Soviet period on the territory of the Nenets Autonomous District, reveals the peculiarities of their influence on the life of the minor indigenous people of Russia – the Nenets. The Nenets are heterogeneous due to their wide area of settlement; therefore, various factors influenced the formation of their religious worldview. The Nenets of the NAO differ from the Nenets living in the Yamalo-Nenets and Taimyr Autonomous Districts not only in their linguistic dialect, but also in their cultural traditions. When considering the Nenets of the NAO, it was revealed that the Soviet secularization influenced them to a greater extent than the Nenets of the Yamalo-Nenets Autonomous District and the Taimyr Autonomous District. Therefore, the purpose of this article is to find out how the Soviet secularization influenced the worldview of the Nenets of the NAO. The methodology of this study is based on the K. Dobbelere’s concept of the three-level model of secularization. The materials of the State Archive of the Nenets Autonomous District, the local newspaper “Naryana Vynder” and the results of the field research on the territory of the Nenets Autonomous District from 2014 to 2019 were used as sources.